Milk Street 365 : the all-purpose cookbook for every day of the year - Kimball, Christopher; Hirsch, J. M.; Locke, Michelle; Yanagihara, Dawn (Voracious, 2024)
"This is Milk Street's new and comprehensive guide to today's recipe repertoire, full of fresh flavors and simple yet game-changing techniques. This is everyday cooking you actually want to cook every day. Milk Street 365 is both inspiration and reference for the contemporary kitchen, with recipes that will change the way you cook at home==from soups, stews and salads to flatbreads, pizzas and noodle."--Amazon.